Տեխնոլոգիական զարգացումը տնտեսության մրցունակության բարձրացման գործոնների համակարգում - Ատոմ, Մարգարյան; Անի Ավետիսյան; Անի Հունանյան (ՀՀ ԳԱԱ հրատ.)
Рассмотрена важная роль развития технологии и инновационной инфраструктуры в повышении конкурентоспособности и активации экономики Армении. Отмечено, что несмотря на недавние международные доклады,которые отмечают небольшой прогресс в сфере технологии, до сих пор эти изменения не являются существенными. С точки зрения технологического развития Армения может иметь серьезные возможности, поскольку эта область имеет огромный потенциал для развития. На пути формировании конкурентоспособной экономики в РА очень важна реализация последовательной и целенаправленной политики.The article discusses the crucial role of technology and innovation infrastructure development in boosting the economic growth in the Republic of Armenia and improving the competitiveness of the nation. The authors mention, that although various reports of last couple of years state that the technology sector of the Republic o Armenia has reported some progress, however, these changes are still not significant. From the point of view of perspectives of development of Armenia’s technology sector, this sector could have serious opportunities due to the huge potential to be utilized. Therefore, in building a competitive economy the Republic of Armenia needs to implement a targeted and sound economic policy.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ